Mesh processing for improved perceptual quality of 3D printed relief. Issue 1 (12th September 2020) - Yang, Yifan; Ohtake, Yutaka; Suzuki, Hiromasa
Abstract: Making arts and crafts is an essential application of 3D printing. However, typically, 3D printers have limited resolution; thus, the perceptual quality of the result is always low, mainly when the input mesh is a relief. To address this problem using existing 3D printing technology, we only operate the shape of the input triangle mesh. To improve the perceptual quality of a 3D printed product, we propose an integrated mesh processing that comprises feature extraction, 3D print preview, feature preservation test, and shape enhancement. The proposed method can identify and enlarge features that need to be enhanced without large-scale deformation. Besides, to improve ease of use, intermediate processes are visualized via user interfaces. To evaluate the proposed method, the processed triangle meshes are 3D printed. The effectiveness of the proposed approach is confirmed by comparing photographs of the original 3D prints and the enhanced 3D prints. Graphical Abstract: